2004
DOI: 10.1159/000080350
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Increases Methionine Synthase mRNA Level in Caco-2 Cells

Abstract: Background: Methionine synthase (MTR) synthesizes methionine from homocysteine, using cobalamin as a cofactor and 5-methyltetrahydrofolate as a cosubstrate. Aim: To determine the influence of homocystine (Hcy, dimer of homocysteine) in the presence of either cobalamin or methionine on the transcription and the activity of methionine synthase in Caco-2, a human adenocarcinoma cell line. Methods: Methionine synthase activity and quantification of its mRNA by real-time RT-PCR were determined in cells cultivated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…As a consequence, it can be concluded that vinblastine sensitivity is a direct consequence of mdr-1 expression in HepG2 cells. A 100 nM cobalamin concentration led to a dramatic increase in MS activity as already shown in cancer intestinal cells [38] and also in about a two log lower GI 50 of vinblastine (Figures 4 and 5). However, the GI 50 of cobalamin (100 nM) ranged above the physiological plasma concentration (0.1 to 1 nM).…”
Section: Discussionsupporting
confidence: 73%
“…As a consequence, it can be concluded that vinblastine sensitivity is a direct consequence of mdr-1 expression in HepG2 cells. A 100 nM cobalamin concentration led to a dramatic increase in MS activity as already shown in cancer intestinal cells [38] and also in about a two log lower GI 50 of vinblastine (Figures 4 and 5). However, the GI 50 of cobalamin (100 nM) ranged above the physiological plasma concentration (0.1 to 1 nM).…”
Section: Discussionsupporting
confidence: 73%
“…Translation of methionine synthase, the enzyme that functions immediately downstream of MTHFR, by transferring the methyl group from 5-methyltetrahydrofolate to homocysteine for the synthesis of methionine, is influenced by a functional internal ribosome entry site element (43). It has also previously been reported that methionine synthase mRNA levels are increased by treatment of cultured cells with Hcy (44).…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine dioxygenase activity is increased in response to increasing levels of dietary methionine at post-transnlational levels due to suppression of degradation of the enzyme via polyubiquitination [7,8]. Methionine synthase levels are increased by homocysteine at the transcriptional level [9]. On the other hand, the activation of glutamate-cysteine ligase in glutathione synthesis is decreased in response to increased levels of dietary protein or methionine [10].…”
Section: The Mercaptopyruvate Pathway and Mercaptopyruvate Sulfurtranmentioning
confidence: 99%